Category Signaling and Reputation - Negro, Giacomo; Hannan, Michael T.; Fassiotto, Magali (Organization Science, 2015)
We propose that category membership can operate as a collective market signal for quality when low-quality producers face higher costs of gaining membership. The strength of membership as a collective signal increases with the sharpness of the category boundary, that is, contrast. Our empirical study focuses on biodynamic and organic viticulture in Alsace.